EFEKTIFITAS INTERACTIVE STORY TELLING DENGAN MEDIA KOMIK DALAM PENCEGAHAN GIGI KARIES PADA ANAK USIA PRE SCHOOL - Istiqomah, Nurul; Sari, Anggi Luckita; Purwaningsih, Heni; Salsabila, Nur Amalina; Lestari, Leni Dwi; Asjad, Syahria Ulayya (Universitas Sam Ratulangi, 2025)
Background : Caries in early childhood is a major oral health problem. Caries affects infants and preschool children worldwide. Factors that influence the incidence of caries in children are the habit of giving sweet, sticky foods and drinking milk, the habit of brushing teeth and the incidence of dental caries so that there is a need for education about the prevention of dental caries. Interactive story telling helps children's development, to help them express and give meaning to the world, to develop communication, recognition and memory skills. Objective : to determine the incidence of dental caries in pre school-aged children and determine the effectiveness of Interactive Story Telling in preventing dental caries in pre school-aged children. Method : This research uses quasi experimental research with one group design. Where researchers use 1 group as the treatment group, which was given intervention in the form of interactive story telling to prevent dental caries, the intervention was given to mother and child pairs. Result : there was a significant difference in knowledge between before and after counseling. Conclusion : interactive story telling that has been carried out is effective in preventing dental caries in pre school-aged children.